INTERVIEW - PROF. MARILYN NAIDOO - R. Venter (Acta Theologica)
Prof. Rian Venter, Dept Historical and Constructive Theology, UFS,  interviewed Prof. Marilyn Naidoo from UNISA regarding her research on theological education in South Africa.